2022
DOI: 10.1002/ange.202215468
|View full text |Cite
|
Sign up to set email alerts
|

(BO)2‐Doped Tetrathia[7]helicene: A Configurationally Stable Blue Emitter

Abstract: Helicenes combine two central themes in chemistry: extended π-conjugation and chirality. Heteroatom doping preserves both characteristics and allows modulation of the electronic structure of a helicene. Herein, we report the (BO) 2 -doped tetrathia[7]helicene 1, which was prepared from 2-methoxy-3,3'-bithiophene in four steps. 1 is formally derived by substituting two (Mes)BÀ O moieties in place of (H)C=C(H) fragments in two benzene rings of the parent tetrathia[7]helicene. X-ray crystallography revealed a dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…For example, boroles can be readily converted into other compounds by expanding their ring structure with unsaturated substrates, a process that helps to reduce the high energy associated with their antiaromatic π-electron system. , In the past decade, boron-containing heterocyclic products of these transformations, such as aromatic 1,2-azaborinines, have garnered attention due to their potential applications as pharmaceutical drugs and active components in optoelectronic devices. The ring expansion of boroles has also emerged as a viable method for synthesizing benzene analogues containing chalcogen atoms, such as 1,2-oxa- and 1,2-thiaborinines. , Notably, the group of Martin demonstrated that the reaction of 1,2,3,4,5-pentaphenylborole with N -methylmorpholine- N -oxide (NMMO) and elemental sulfur (S 8 ) led to the formation of the respective 1,2-oxa- and 1,2-thiaborinine derivatives I and II (Scheme ). Another example by the Wagner group involved the use of oxygen as a chalcogen source, resulting in the synthesis of a 10,9-oxaboraphenanthrene derivative through the ring expansion of a dibenzoborole (i.e., 9-borafluorene) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, boroles can be readily converted into other compounds by expanding their ring structure with unsaturated substrates, a process that helps to reduce the high energy associated with their antiaromatic π-electron system. , In the past decade, boron-containing heterocyclic products of these transformations, such as aromatic 1,2-azaborinines, have garnered attention due to their potential applications as pharmaceutical drugs and active components in optoelectronic devices. The ring expansion of boroles has also emerged as a viable method for synthesizing benzene analogues containing chalcogen atoms, such as 1,2-oxa- and 1,2-thiaborinines. , Notably, the group of Martin demonstrated that the reaction of 1,2,3,4,5-pentaphenylborole with N -methylmorpholine- N -oxide (NMMO) and elemental sulfur (S 8 ) led to the formation of the respective 1,2-oxa- and 1,2-thiaborinine derivatives I and II (Scheme ). Another example by the Wagner group involved the use of oxygen as a chalcogen source, resulting in the synthesis of a 10,9-oxaboraphenanthrene derivative through the ring expansion of a dibenzoborole (i.e., 9-borafluorene) .…”
Section: Introductionmentioning
confidence: 99%
“…42 Introducing heteroatoms and non-hexagonal rings into the framework of helicenes could provide new design strategies to manipulate the chiroptical properties. 24,[43][44][45][46][47] The dopants consisting of boron and nitrogen atoms have proved to an effective tool of manufacturing new chiral materials with superior chiroptical responses due to the isoelectronic relationship between BN unit and carbon-carbon (CC) unit, 23, 48-51 while structural defects have been exploited much less in helicenes compared to in nanographenes. In addition, nitrogen-boron-nitrogen (NBN) unit has been utilized to stabilize the zigzag edges of nanographenes.…”
mentioning
confidence: 99%